Застосування електронних колориметрів для експрес-аналізу якості води - Гусак, О. А. (ХНУРЕ, 2024)
This work explores the use of portable electronic colorimeters for rapid water quality analysis on-site. It discusses their importance in various applications such as aquaculture monitoring and water source assessment. The benefits of electronic colorimeters, including speed and accuracy, are emphasized, highlighting their role in eliminating the need for sample transportation to laboratories. The necessity of field testing for reliable results and the basic equipment required for such analysis are outlined. Overall, the study concludes that mobile electronic colorimeters offer an efficient and economical approach to water quality analysis
Keywords: електронний колориметр; експрес-аналіз якості води